The Best Question: Explaining the Projection Behavior of Factives. Issue 3 (3rd April 2017) - Simons, Mandy; Beaver, David; Roberts, Craige; Tonhauser, Judith
Abstract : This article deals with projection in factive sentences. The article first challenges standard assumptions by presenting a series of detailed observations about the interpretations of factive sentences in context, showing that what implication projects, if any, is quite variable and that projection is tightly constrained by prosodic and contextual information about the alternatives under consideration. The article then proposes an account which accommodates the variability of the data and sensitivity to contextual alternatives. The account is formulated within a modified version of Roberts 1996/2012 question-based model of discourse.